2018
DOI: 10.3892/ol.2018.9305
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA PVT1 expression inhibits proliferation and migration by regulating p38 expression in prostate cancer

Abstract: Long non-coding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) has been reported to be overexpressed in prostate cancer cells and associated with tumorigenesis in various types of cancer. However, the biological function of lncRNA PVT1 remains largely unknown. The aim of the present study was to investigate the effect of lncRNA PVT1 expression on the proliferation and migration of prostate cancer cells. Stably transfected prostate cancer cells with downregulated expression of lncRNA PVT1 were constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Located at the 8q24 chromosomal region, the long nonprotein-coding gene PVT1 has been shown to be overexpressed in various cancers including PCa, breast, pancreatic, lung, and gastric cancers. Downregulation of expression of the long noncoding RNA (lncRNA) from PVT1 inhibits proliferation and migration by regulating p38 expression in PCa [19]. Increasing evidence has shown the important role of lncRNAs in many different biological processes [23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Located at the 8q24 chromosomal region, the long nonprotein-coding gene PVT1 has been shown to be overexpressed in various cancers including PCa, breast, pancreatic, lung, and gastric cancers. Downregulation of expression of the long noncoding RNA (lncRNA) from PVT1 inhibits proliferation and migration by regulating p38 expression in PCa [19]. Increasing evidence has shown the important role of lncRNAs in many different biological processes [23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified PVT1 as being procarcinogenic and have shown that PVT1 amplification increases the risk of PCa incidence [5,9,19]. We previously demonstrated that the transcript from exon 9 of PVT1 may be involved in PCa, but the underlying molecular mechanisms were unknown [7].…”
Section: Introductionmentioning
confidence: 96%
“…Data from many sources suggest that PVT1 is a major contributor to the development of prostate cancer (81,82). A CCK-8 (Cell Counting Kit-8) assay assessment of the effect of PVT1 downregulation in PC3 and DU145 cells showed an inhibition of cell proliferation (83). Confirming this effect in the same study, PVT1 downregulation also reduced the size of tumors in mice.…”
Section: Pvt1 In Prostate Cancermentioning
confidence: 54%
“…LncRNA SNHG7 can affect miR-503/Cyclin D1 pathway then regulate the viability and cycle progression of PC cells (32). The down-regulation of lncRNA PVT1 can regulate p38 expression then decrease PC cells metastasis (33). In addition, it has been reported that lncRNA HOTAIR and MALAT1 affect transcriptional regulation in PC cells induced by estrogen (34).…”
Section: Discussionmentioning
confidence: 99%